Natural host range, incidence on overwintering cotton and diversity of cotton leafroll dwarf virus in Georgia USA. (June 2021) - Sedhain, Nabin P.; Bag, Sudeep; Morgan, Kaelyn; Carter, Richard; Triana, Patrick; Whitaker, Jared; Kemerait, Robert C.; Roberts, Phillip M.
Abstract: In 2018–19, cotton leafroll dwarf virus (CLRDV) was reported from several cotton-producing states in the southern United States. An extensive survey was conducted in the spring, summer, and fall of 2019 to identify weeds and overwintering cotton as sources for primary inoculum for the next season crop. Foliage samples of 57 different weed species were collected from fields formerly planted to cotton and analyzed using RT-PCR with CLRDV specific primers. CLRDV was detected from 23 weed species belonging to 16 different botanical families. Overwintering cotton stalks (48%) and regrowth leaves (75%) both harbored CLRDV. A phylogenetic analysis conducted using nucleotide and amino acid sequences of complete ORF 0, ORF 3, and ORF 4 determined that the CLRDV from all weeds and overwintered cotton stalks from Georgia clustered with CLRDV isolates collected in the USA but differed from isolates reported from South America and Asia. Pairwise nucleotide and amino acid identity showed 91–100% sequence similarity for complete ORF3. For ORF4, pairwise identity among the nucleotide ranged from 92-100%, while amino acids ranged from 90.2-100% with isolates reported from the USA and South America, with the exception of three Asian CLRDV isolates and two weed isolates from Georgia. Similarly, CLRDV isolates from Georgia weeds shared 91.6–93% nucleotide and 88–90.8% amino acid for silencing suppressor compared to most of the isolates from North America and South America. The role of alternative hosts on disease incidence and spread has not been studied in cotton-producing countries where the disease is prevalent. This is the first comprehensive study that identifies weeds and overwintering cotton as a potential green bridge for the year-round survival of CLRDV. Highlights: Natural infection of CLRDV was detected from 23 weeds species belonging to 16 families. CLRDV was detected in 48% of overwintering cotton stalks. Seventy-five percentage of cotton regrowth harbor CLRDV. Field sanitation and removing of cotton stalks may reduce the primary virus inoculum.